2017
DOI: 10.4103/sja.sja_292_17
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided multilevel paravertebral block versus local anesthesia for medical thoracoscopy

Abstract: Background:Local anesthetic infiltration for medical thoracoscopy has an analgesic properties for short duration. Single injection thoracic paravertebral block (PVB) provides limited analgesia.Purpose:Comparison between thoracic PVB performed at two or three levels with local infiltration for anesthetic adequacy in adult medical thoracoscopy as a primary outcome and postthoracoscopic analgesia and pulmonary function as secondary outcomes for adult medical thoracoscopy.Patients and Methods:Prospective randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…[13] Thoracic paravertebral block has superior analgesia and lung function, as well as fewer complications than systemic opioids. [14,15] It has been successfully applied in sternotomy, breast surgery, abdominoplasty, and laparoscopic cholecystectomy. [1619]…”
Section: Introductionmentioning
confidence: 99%
“…[13] Thoracic paravertebral block has superior analgesia and lung function, as well as fewer complications than systemic opioids. [14,15] It has been successfully applied in sternotomy, breast surgery, abdominoplasty, and laparoscopic cholecystectomy. [1619]…”
Section: Introductionmentioning
confidence: 99%
“…There has also been recent interest in the role of regional nerve blocks performed by anesthesiologists to reduce both intraoperative and postoperative pain as well as reduce the amount of sedatives and narcotics used during the procedure. Most commonly studied blocks included paravertebral block [43], midpoint transverse block [44], erector spinae block [45,46 && , [47][48][49], Although these studies have demonstrated feasibility and safety as well as reduction in postoperative pain, the exact role of regional anesthetic techniques in efficacy for optimizing outcomes in patients undergoing pleuroscopy remains under active investigation [35 & ]…”
Section: Andandmentioning
confidence: 99%
“…However, pain at a distant site of parietal pleural biopsy can only be mitigated with systemic analgesia. This is where various regional anesthesia blocks during medical thoracoscopy have been appealing and are being studied, such as paravertebral block [11,12] and erector spinae plane block [13][14][15][16]. Serratus anterior plane block [17 & ] and intercostal nerve block have been studied in thoracoscopic surgeries and yet to be studied in medical thoracoscopy.…”
Section: Anesthesiamentioning
confidence: 99%